Reducing Methane Emissions in Ruminant Production: Methods and Their Impacts - Zhang Zifang (E3S Web of Conferences)
Introduction: Greenhouse gases contribute significantly to the greenhouse effect, with methane being one of the primary gases. Methane emissions largely stem from ruminant production. Reducing methane emissions from ruminants is beneficial for the environment and improves the feed efficiency of the animals. This article examines the process by which cattle produce methane in the rumen through enteric fermentation and how this methane is subsequently released into the atmosphere. Additionally, various methods to mitigate methane emissions from ruminants are summarized. Main text and discussion: Several methods to address methane emissions from cattle were discussed. First, feed additives: Adding certain compounds or biological extracts to cattle feed can significantly reduce methane emissions. Second, efficient feeding management: Intensive management strategies, such as feeding cattle at specific times, can minimize energy loss and improve feed efficiency. Third, genetic methods: Genomic selection can be used to select animals with lower methane emissions, and gene editing tools can be employed to modify the genes of cattle. Breeding varieties that produce less methane, such as miniature cows, were also considered. The advantages and disadvantages of each biological solution were summarized. Furthermore, political and economic strategies that could potentially replace conventional beef were explored. Conclusion: The greenhouse effect caused by greenhouse gases presents a major challenge that requires a multifaceted approach. Genetic engineering, including gene editing, shows promise but is still developing. Feed additives can reduce ruminant methane emissions, while legislative measures can improve economic structures. Cultured or alternative meats can serve as substitutes for ruminant meat. Although each method has limitations, combining them may yield the best results.